A Changing Perspective on the Role of Neuroinflammation in Alzheimer's Disease. (15th July 2012) - Wilcock, Donna M.
Abstract : Alzheimer's disease (AD) is a complex, neurodegenerative disorder characterized by the presence of amyloid plaques and neurofibrillary tangles in the brain. Glial cells, particularly microglial cells, react to the presence of the amyloid plaques and neurofibrillary tangles producing an inflammatory response. While once considered immunologically privileged due to the blood-brain barrier, it is now understood that the glial cells of the brain are capable of complex inflammatory responses. This paper will discuss the published literature regarding the diverse roles of neuroinflammation in the modulation of AD pathologies. These data will then be related to the well-characterized macrophage phenotypes. The conclusion is that the glial cells of the brain are capable of a host of macrophage responses, termed M1, M2a, M2b, and M2c. The relationship between these states and AD pathologies remains relatively understudied, yet published data using various inflammatory stimuli provides some insight. It appears that an M1-type response lowers amyloid load but exacerbates neurofibrillary tangle pathology. In contrast, M2a is accompanied by elevated amyloid load and appears to ameliorate, somewhat, neurofibrillary pathology. Overall, it is clear that more focused, cause-effect studies need to be performed to better establish how each inflammatory state can modulate the pathologies of AD.